Mechanical, Structural and Physical Properties of Carrageenan-Gum Arabic Biocomposite Film for Hard Capsule Application - Nur Amalina, Ramli; Nurul Natasya Amira, Kamaluddin; Fatmawati, Adam (Trans Tech Publications Ltd, 2022)
The hard capsule market growth is mainly driven by the demand for gelatin capsules made of animals. Plant-based hard capsules, such as hydroxypropyl methylcellulose are currently in high demand for drug delivery, but the manufacturing process is costly with limited reagent supply. As an alternative, carrageenan from seaweed was used as a film-forming agent in this work. Carrageenan film possesses low mechanical strength, thus gum Arabic is incorporated to strengthen the biocomposite film. The films and hard capsules were produced with different concentrations of gum Arabic, ranging from 0 to 2.0 w/v%. The tensile strength and elongation at break were enhanced to 56.8 MPa and 23.7%, respectively. The highest capsule loop strength is 32.5 N, which was achieved at 1.2 w/v% of gum Arabic. All biocomposite films were kept at a moisture content of 13%, which is comparable to gelatin hard capsules. These results demonstrate that gum Arabic can strengthen the carrageenan biocomposite to be an alternative to gelatin hard capsules.